Factors Influencing Crop Diversification in Tirunelveli District of Tamil Nadu - L., Mohammed Ghouse; Hassan, S. Nazreen (Indian Journal of Extension Education, 2020)
To cope up with the risk involved in mono cropping system, a shift in cropping pattern, from traditionally grown less benefit crops to more benefit crops can be used as a strategy to increase the income as well as agricultural sustainability. It reduces the risk to farmer from total crop failure by providing alternative means of income through other crops grown. It also helps in conservation of natural resources, increases food and nutritional security and helps in poverty alleviation by providing employment opportunities to the farmers. This paper analyzes the factors influencing crop diversification in Tirunelveli district of Tamil Nadu. We studied the factors influencing crop diversification in using the primary data. Non – Experimental Research design was used and a sample size of 120 respondents was selected using proportionate random sampling technique. Out of twenty two variables, family size, distance to the market, economic motivation, risk orientation, innovativeness and scientific orientation had positive and significant association with crop diversification at one per cent level of significance.
Keywords: Crop diversification; Credit orientation; Factors; Family size; Scientific orientation